A critical note on the evolution of social theoretical and linguistic underpinnings of contemporary discourse studies - Cap, Piotr (Array, 2019)
This paper gives a critical overview of analytical approaches dominating the field of discourse studies in the last three decades, from the perspective of their philosophical and formative bases: social constructionism and linguistics. It explores different conceptions of the theoretical nexus between these two bases leading to the emergence of three distinct yet complementary strands of thought (i–iii). The paper starts with poststructuralist views of discourse salient in (i) Laclau and Mouffe’s Discourse Theory. Laclau and Mouffe’s assumption that no discourse is a closed entity but rather transformed through contact with other discourses is taken as the introductory premise to present a large family of (ii) critical discourse studies, characterized as text-analytical practices explaining how discourse partakes in the production and negotiations of ideological meanings. Finally, the paper discusses (iii) three recent discourse analytical models: Discourse Space Theory, Critical Metaphor Analysis, and Legitimization-Proximization Model. These new theories make a further (and thus far final) step toward consolidation of the social-theoretical and linguistic bases in contemporary discourse studies. The empirical benefits of this consolidation are discussed in the last part of the paper, which includes a case study where the new models are used in the analysis of Polish anti-immigration discourse.